The Impact of Technological Developments on the Evolution of Specific Fields of Legislation - Rahmawan, Ardianto Budi (Közigazgatási és Infokommunikációs Jogi PhD Tanulmányok, 2025)
This article examines how technological advancements have influenced the evolution of legislative frameworks in Indonesia and Hungary, focusing on data protection and e-government initiatives. The comparative analysis reveals that while both countries acknowledge similar challenges, they have adopted distinctly different regulatory approaches. Hungary's legislation demonstrates deep integration with European Union frameworks, resulting in comprehensive harmonization, while Indonesia has developed a more autonomous approach tailored to its unique context. This comparison provides valuable insights into how different legal systems navigate the complex intersection of technology and law, offering lessons for jurisdictions facing similar challenges.